Multi-scale microstructure high-strength titanium alloy lattice structure manufactured via selective laser melting. Issue 37 (29th June 2021) - Yang, Xin; Ma, Wenjun; Gu, Wenping; Zhang, Zhaoyang; Wang, Ben; Wang, Yan; Liu, Shifeng
Abstract : The tensile performance of Ti6Al4V alloy lattice structure was investigated. Abstract : The tensile performance of Ti6Al4V alloy lattice structure was investigated. Firstly, a face center cubic unit cell with vertical struts (F2CCZ) lattice structure was designed. Then, the structures were fabricated by selective laser melting (SLM) with different aspect ratios. Subsequently, the SLM-ed alloys were subjected to double solution-aging to homogenize the microstructure and release residual stress. It is shown that there is only acicular α′ martensite with high dislocation density in the SLM-ed alloy, while the heat-treated alloy has α and β phases (there are multi-scale α laths and nano-scale β particles), and the orientation relationship between the two phases is: [113]β //[1210]α . The tensile strength of the HT-ed alloys presents a significant increase from 140 ± 18 MPa in the SLM-ed state to 229 ± 5.1 MPa with an aspect ratio of 4. It indicates that the special heat treatment regime can not only homogenize the microstructure of the SLM-ed alloy, but also improve the tensile strength.